EEC and Yugoslav cooperation in the frames of modern international relations in Europe - E. G. Entina (Vestnik MGIMO-Universiteta)
Traditionally the phenomenon of the European integration towards South East Europe is regarded starting from the XXI century. The explanation for such a periodization are resolution of the open conflicts on the territory of the former Yugoslavia and implementation of the complex EU strategy for the region. Starting point of the majority of researches is the year of 2003 when the EU Agenda for the Western Balkans was started in Thessaloniki. The topic of EEC-Yugoslavia relations, SFRY having been first socialist country to institutionalize its trade and economic relations with Brussels, are unfairly ignored in domestic and foreign scientific literature. It is regarded solely as a chronological period of trade agreements. Nevertheless, this issue is of fundamental importance for understanding the current neighborhood of the European Union. The main thesis the author proves is that in the 1960s and 1980s as it is the case nowadays, the main imperative of Brussels' policy towards the Balkans was to prevent Moscow from increasing its influence. This led to the formation of a very specific format of relations with Belgrade and was one of the reasons why the economic crisis in Yugoslavia became extreme and its economy irreformable. In addition, at a later and structurally much more complicated stage of relations between the countries of the former Yugoslavia and the European Union the specificity and main components of relations of the Cold War period did not fundamentally change. As for the policy of so-called containment of the external actors one could see that besides Moscow, we can speak about similar attitude of the EU towards China. It makes it possible to consider the EU policy towards the countries of the former Yugoslavia in the paradigm of neoclassical realism, rather than in the paradigm of traditional liberal European integration approaches which allows us to unite neorealists elements with the specifics of internal processes, including the modernization of institutes, relations between society and state, types of political leadership.